Penerapan nilai wajar dalam penilaian aset perusahaan perbankan swasta sebelum dan saat pandemi pada Bank Permata Tbk tahun 2019-2020 - Damayyanti, Delvi; Zatayumni, Jihan Fadlilah; Dewa, Mahesa; Sollihah, Putri Dzakiyyah; Fahreza, Rizki Aria (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The application of IFRS in the banking sector plays an important role in seeing its effect on increasing economic growth in Indonesia. One of the banks that have adjusted to IFRS standards by disclosing fairness in their financial statements is Bank Permata. Assessment techniques used to maximize the use of relevant inputs that can be observed. This research was conducted using descriptive analysis to process quantitative data with the application of fair value with assets at PT Bank Permata Tbk. The financial statements use secondary data with data analysis. Overall, the results of the measurement of the fair value of assets from the banking industry at PT Bank Permata Tbk are considered feasible, this is due to the number of statements, namely 19 out of 20 statements that are in accordance with PSAK 68. Based on the results of the analysis, it was found that number 12 does not comply with PSAK 68 paragraph 74 concerning entities prioritizing the hierarchy of values over inputs, on the other hand, according to PSAK 68 paragraph 74 the priority is inputs over fair value hierarchies.